Integration of Qur’anic Values in Family Counseling Practices - Barry, Aboubacar; Salim, Hakmuddin (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study examined the integration of Qur’anic values in family counseling practice as a holistic response to the demands on contemporary families. This study emerged from a growing need for counseling models to incorporate spiritual guidance to foster resilience, cohesion, and ethical accountability. The study aims to analyze how Qur’anic values such as compassion, justice, patience, and forgiveness can be systematically applied to promote family dynamics and enhance the role of counselors professionally. Using qualitative, descriptive, and documentary analysis, the research included textual and theme analysis of Qur’anic verses, Hadith, traditional interpretations of the Qur’an, and more recent approaches to counseling. The results were structured around three interconnected dimensions: first, the significance of value-like teaching to enable practitioners to integrate Qur’anic ethics within therapy; second, that families convey moral values both explicitly and implicitly which often involves children holding parents accountable and acting as enforcers of outcomes; and third, that participants perceived positive integration of healing Qur’anic values into family life that included improving conflict resolution, intergenerational respect, and community cohesion. The study showed that although embedding Qur’anic values in psychological counseling is not limited to providing not only culturally appropriate and spiritually affirming advice, but also modern psychological practices into a socialization process that includes a holistic paradigm of human well-being that involves mind, body, and spirit. In summary, integrating Qur’anic values into counseling represents a paradigm shift that can strengthen familial relationships, enable counselors, and contribute to the moral integrity of society.